Legalitas Covernote yang Dikeluarkan oleh Notaris dalam Putusan Mahkamah Agung Nomor 4242 K/PID.SUS/2023 - Buana Shyntia Rani (CV Rewang Rencang, 2025)
The covernote issued by a notary is a statement letter that falls outside the scope of the notary's official authority and does not constitute a legal product of the notary. The authority to issue a covernote is not regulated by any existing laws or regulations. Based on the Supreme Court Decision Number 4242 K/Pid.Sus/2023, a notary was found guilty of committing a criminal act of corruption for abusing their authority as a notary, in accordance with Article 3 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption, in conjunction with Article 56 paragraph (1) of the Indonesian Penal Code. The issuance of a covernote by a notary is typically done at the request of a bank in relation to deeds and documents for the provision of credit facilities. Therefore, in such cases, the notary may also be subject to administrative sanctions for maladministration.